2013
DOI: 10.1063/1.4797488
|View full text |Cite
|
Sign up to set email alerts
|

Rate limiting step for the switching kinetics in Cu doped Ge0.3Se0.7 based memory devices with symmetrical and asymmetrical electrodes

Abstract: We report on the comparison of the resistance switching properties and kinetic behavior of Cu doped Ge0.3Se0.7 solid electrolyte based dual layer memory devices integrated with asymmetrical (Pt and Cu) and symmetrical electrodes (only Cu). In spite of the fact that the observed resistance switching properties and its parameters are quite similar for both memory devices, the dependence of the SET-voltage on the voltage sweep rate suggests different microscopic rate limiting factors for the resistance switching … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 27 publications
0
4
0
Order By: Relevance
“…The counter electrode is an inert electrode such as Pt, Ir, and TiN, and should not be able to dissolve and electrochemically react during the switching processes. In addition, SiO 2 is often used as a barrier (or second layer), significantly improving the device characteristics . SiO 2 ‐based ECM devices were reported to switch at very low currents and low power, to be fast, extremely stable against radiation and can operate at temperatures as low as 7 K …”
Section: Extrinsic Switching: Electrochemical Reactions and Ecm Resismentioning
confidence: 99%
“…The counter electrode is an inert electrode such as Pt, Ir, and TiN, and should not be able to dissolve and electrochemically react during the switching processes. In addition, SiO 2 is often used as a barrier (or second layer), significantly improving the device characteristics . SiO 2 ‐based ECM devices were reported to switch at very low currents and low power, to be fast, extremely stable against radiation and can operate at temperatures as low as 7 K …”
Section: Extrinsic Switching: Electrochemical Reactions and Ecm Resismentioning
confidence: 99%
“…In contrast, σ ion denotes the ionic conductivity of the ion con-Fig. 2 FEM model for calculation of electric potential φ and currents based on solving the stationary electric continuity equation for electrode (φ 1 ) and electrolyte domains (φ 2 ) according to eqn ( 8) and (9). At the electrolyte/(Ag)-electrode interfaces the Butler-Volmer equation serves as a boundary condition, leading to the reaction overpotentials η (cf.…”
Section: Calculation Of the Electric Potentialmentioning
confidence: 99%
“…Typically, an ECM cell consists of an ion conducting insulating layer sandwiched between an electrochemically active electrode such as Ag or Cu and an inert counter electrode. 5,6 Thereby, solid electrolytes such as GeS x 7, 8 , GeSe 9,10 or AgI, 11,12 or metal oxides such as Ta 2 O 5 , 13 SiO 2 , 14,15 or 16 can serve as ion-conducting layer. If a positive voltage is applied to the active electrode, the active electrode is oxidized, Ag/Cu ions are injected into the insulating material and migrate in direction of the electric field.…”
Section: Introductionmentioning
confidence: 99%
“…It is found that the required switching electrical fields for SET and RESET of the CuI memristor are comparable to those of ECM memristors based on chalcogenides. [ 24,37–63 ] As these ECM memristors based on solid electrolyte (the area covered by the pink circle in Figure 1h) generally shows the lowest power consumption compared to their counterparts, the CuI memristor is promising for implementing low‐power in‐memory computing architecture. [ 26 ] At the same time, the fabrication processes for the reported ECM memristors are based on vacuum‐based deposition techniques.…”
Section: Resultsmentioning
confidence: 99%